A review of the genus Scirpophaga Treitschke, 1832 in China (Lepidoptera: Pyralidae) - Chen, Fuqiang; Song, Shimei; Wu, Chunsheng (Zootaxa, 2006)
Twenty species of the genus Scirpophaga are recognized from China; six are reported for the first time, and two are described as new: S. linguatella, sp. n., and S. adunctella, sp. n. Scirpophaga melanostigma is proposed as a synonym of S. flavidorsalis, syn. n. Keys to the species recorded from China are provided. The adults of the new species and the genital structures of all examined species are illustrated. The types of the new species and other specimens examined are deposited in the Institute of Zoology, Chinese Academy of Sciences, Beijing.